The Urgency of Patriotism in Maintaining the Unity in the Republic of Indonesia in the Perspective of Maslahah - Zezen Zainul Ali (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2021)
ABSTRACTPatriotism is the willingness of a citizen to protect the country to maintain national unity. Love for the homeland or patriotism often creates pros and cons in its interpretation. Then, it needs to raise awareness as a step to prevent conflicts that arise and consequently cause divisions within the country. The emergence of interpretations between Patriotism and religion that they cannot be combined, so they have willing to change the state ideology to other ideology, such as khilafah ideology through the emergence of radicalism, extremism, and separatism groups. The research was a literature review using literature data from related books and articles. Data analysis used a qualitative analysis. This study was expected to become a scientific treasure and be practiced in the life of the nation and state. Patriotism explicitly does not available stated in either the Qur'an or Hadith. However, in principle, Islamic law will always answer the problems to provide benefits for mankind, which is the maslahah. Having a love for the homeland is mubah (permitted), but it may switch to be mandatory during emergencies and conditions. This attitude of love for the homeland is in the condition of daruriyah.Keywords: Patriotism, Maslahah, Daruriyah.ABSTRAKPatriotisme merupakan kerelaan seseorang warga negara demi menjaga negaranya guna untuk menjaga persatuan bangsa, rasa cinta tanah air atau patriotisme sering kali menimbulkan pro kontra dalam penafsirannya, maka diperlukan pemulihan kesadaran sebagai langkah awal pencegahan konflik yang timbul dan akibatnya menimbulkam perpecahan dalam negara, munculnya penafsiran antara patriotisme dan agama itu tidak dapat menyatu sehingga menginginkan untuk menganti ideologi negara menadi ideologi khila>fah dengan bermuculanya kelompok radikalisme, ektrimisme dan separarstisme. Penelitian ini merupakan pustaka yang dikaji menggunakan data-data literatur yang berasal dari buku dan artikel terkait dan dianalisis secara kualitatif. Kajian ini diharapkan menjadi suatu khasanah keilmuan dan dapat dipraktikkan dalam kehidupan berbangsa dan bernegara. Patriotisme secara eksplisit belum ada baik dalam al-Qur’an maupun hadis. Akan tetapi prinsipnya hukum Islam akan selalu menjawab persoalan-persoalnan yang muncul untuk memberikan kemaslahatan bagi umat manusia yakni mencapai maslahah. Pada dasarnya memiliki rasa cinta kepada tanah air adalah boleh atau mubah akan tetapi hal tersebut bisa menjadi wajib saat situasi dan kondisi yang memang darurat. Sikap cinta tanah air dalam keadaan yang daruriyah.Kata Kunci: Patriotisme, Maslahah, Daruriyah.